INTERNET OF THINGS IN EDUCATION (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The article discusses the introduction of the Internet of things in the educational sphere, which will help in the development of future professional activities. In this article, we saw the many applications of IoT in the education sector and discussed the various benefits that students and educators receive from the built-in IoT ecosystem. By integrating sensors and mobile devices into a building, IoT can transform classrooms.